2007
DOI: 10.1001/archsurg.142.2.150
|View full text |Cite
|
Sign up to set email alerts
|

LigaSure vs Clamp-and-Tie Technique to Achieve Hemostasis in Total Thyroidectomy for Benign Multinodular Goiter

Abstract: Occurrence of adverse effects and advantages of the LigaSure diathermy system (or LigaSure vessel sealing system) in total thyroidectomy have not been tested in prospective randomized studies comparing its use with that of the time-saving clamp-and-tie technique to ligate and divide thyroid vessels. The effectiveness of LigaSure in achieving vessel division and hemostasis remains dependent on vessel diameter, and the risk of damage to adjacent structures cannot be completely excluded. We tested the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…However, the publications are inconsistent on the issue. Saint Marc and colleagues have reported that the cost of a single procedure with the use of LVSS increased by EUR 45 as compared with classical haemostatic techniques (16). An increase in the costs of thyroid surgery with the use of LVSS has also been noted by Cipolla and colleagues (14).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the publications are inconsistent on the issue. Saint Marc and colleagues have reported that the cost of a single procedure with the use of LVSS increased by EUR 45 as compared with classical haemostatic techniques (16). An increase in the costs of thyroid surgery with the use of LVSS has also been noted by Cipolla and colleagues (14).…”
Section: Discussionmentioning
confidence: 91%
“…the limitation to 1.5-2 cm of the range of heat action on surrounding tissues. However, not all publications report a drop in the number of complications: Saint Marc and colleagues have demonstrated a total percentage of complications at 35% (including transient complications) and no statistically significant difference between the group undergoing surgery with the use of LVSS and the one with a classical technique (16).…”
Section: Discussionmentioning
confidence: 99%
“…Saint Marc et al in his prospective study of 200 patients found that 1 patient in the LigaSure group ( n = 100) and 2 patients in the clamp-and-tie group ( n = 100) required revision surgery due to hematoma. Despite this, the authors considered LigaSure to be as safe as the clamp-and-tie technique [11]. Franko et al obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Two other randomized trials with larger patient numbers have been published during the period of patient inclusion of the present study [4,5]. In both trials a total, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…bilateral thyroidectomy, was done, and both studies reported a time saving effect when the LigaSure was used (see Figure 2). Saint Marc et al concluded however that the time saving was clinically hardly relevant: 41 minutes when using the ligasure versus 49 when using conventional suture ligations [5]. Although this absolute gain of approximately seven and a half minute does not appear to be clinically significant, the total operative time has to be taken into account.…”
Section: Discussionmentioning
confidence: 99%